THEORETICAL FOUNDATIONS FOR THE DEVELOPMENT OF EDUCATIONAL MODELS IN TEACHER TRAINING TECHNOLOGIES - Anarkulova Gulnaz Mirzaxmatovna (Western European Studies, 2024)
The article reveals the essence of the theoretical foundations of educational models. The functions of educational modeling and the results of research on the development of educational models are also considered.
Keywords: modeling; educational models; functions of educational models; models